(untitled) (PANGEEA, 2026)
The National Cadastre and Land Registry Program (PNCCF), initiated in 2015, is still ongoing and is being implemented with non-reimbursable European funds and from the state, the purpose of this project is the free registration of all properties in Romania in the integrated cadastre and functional registry system, the creation of the cadastral administrative plan and the opening of the functional registers in Romania to everyone. In order to carry out the reception work of the technical documents of the systematic cadastre, we chose Cadastral Sector no. 31 from the Territorial Administrative Unit of Papiu Ilarian commune in Mures county. Sector no. 31 is located both in the built-up area and in the extra-built area of the locality with a plateau relief and a predominant use category of arable land. Sector 31 includes a number of 71 buildings, each with a different identifier ranging from 31000 to 31071.